2018
DOI: 10.1371/journal.pone.0199852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host species and environmental factors on the prevalence of Batrachochytrium dendrobatidis in northern Europe

Abstract: The fungal pathogen Batrachochytrium dendrobatidis (Bd) poses a major threat to amphibian populations. To assist efforts to address such threats, we examined differences in Bd host infection prevalence among amphibian species and its relations to both local environmental factors in breeding habitats and landscape variables measured at three scales (500, 2000 and 5000 m radii) around breeding sites in southernmost Sweden. We sampled 947 anurans of six species in 31 ponds and assessed their infection status. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…If river densities are low, Bd mean intensity increases slightly when precipitation levels are low with our observations of higher prevalence in populations expe- (Kriger, Pereoglou, & Hero, 2007;Ron, 2005), and field studies indicating that Bd outbreaks might be more likely under wet conditions (Bosch et al, 2007;Lips et al, 2006). Yet, no published study has linked infection intensity with a reduction in either (a) the size of water basin (hydroshed area) or (b) the density of river networks (however, see Kärvemo et al, 2018;Spitzen-van der Sluijs, Canessa, Martel, & Pasmans, 2017). We found that as hydroshed area increased, infection intensity decreased slightly, suggesting that R. pipiens populations concentrated within a small drainage basin may facilitate the proliferation and transmission of zoospores, as increasing host population density increases transmission rates (Briggs et al, 2010).…”
Section: Intensity Of Infection (Mean Ge) Was Negatively Correlated Withsupporting
confidence: 48%
See 1 more Smart Citation
“…If river densities are low, Bd mean intensity increases slightly when precipitation levels are low with our observations of higher prevalence in populations expe- (Kriger, Pereoglou, & Hero, 2007;Ron, 2005), and field studies indicating that Bd outbreaks might be more likely under wet conditions (Bosch et al, 2007;Lips et al, 2006). Yet, no published study has linked infection intensity with a reduction in either (a) the size of water basin (hydroshed area) or (b) the density of river networks (however, see Kärvemo et al, 2018;Spitzen-van der Sluijs, Canessa, Martel, & Pasmans, 2017). We found that as hydroshed area increased, infection intensity decreased slightly, suggesting that R. pipiens populations concentrated within a small drainage basin may facilitate the proliferation and transmission of zoospores, as increasing host population density increases transmission rates (Briggs et al, 2010).…”
Section: Intensity Of Infection (Mean Ge) Was Negatively Correlated Withsupporting
confidence: 48%
“…infectivity and virulence; O'Hanlon et al, 2018), and the surrounding abiotic and biotic environment (e.g. environmental heterogeneity and landscape structure; Kärvemo, Meurling, Berger, Höglung, & Laurila, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chytridiomycosis is a disease that has impacted amphibians in a wide range of environmental conditions (21,60). Past studies have attempted to link Bd phenotypic patterns with environmental factors in order to understand how abiotic factors might mitigate or exacerbate disease (5,30,43,61). For example, both Becker et al (30) and Greener et al (21) documented considerable phenotypic variation for isolates within the BdGPL that was associated with differential pathogenicity in common susceptible host species (Lithobates sylvaticus and Alytes obstetricans, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The Bd‐positive ponds are all located within one region of our study area, although they are dispersed in the landscape in‐between Bd‐negative ponds. We cannot exclude the presence of false negatives in our data (Erickson et al., 2019) as eDNA is known to show “patchy distributions” within environments, but a similar distribution pattern has also been found in other countries, such as Sweden (Kärvemo et al., 2018) and the UK (Smith, 2014), that both have hosted Bd for a longer time. Also, in Sweden, the number of ponds with Bd is increasing in line with increasing monitoring time, suggesting that a larger Norwegian sample size and/or sampling at more optimal sampling times would result in a higher number of positive ponds in the Bd‐positive area (Kärvemo et al., 2018).…”
Section: Discussionmentioning
confidence: 60%